Experiences from intrathecal baclofen treatment based on medical records and patient- and proxy-reported outcome: a multicentre study. Issue 9 (24th April 2019) - Gunnarsson, Stina; Alehagen, Siw; Lemming, Dag; Ertzgaard, Per; Ghaderi Berntsson, Shala; Samuelsson, Kersti
Abstract: Purpose : To investigate patient satisfaction with intrathecal baclofen treatment, complications from the treatment, and the impact of general expectations on treatment outcome in relation to satisfaction. Methods : A multicentre study with cross-sectional design. Data were collected through questionnaires and patient records. Patients were recruited from six outpatient intrathecal baclofen clinics in Sweden. Eighty-three patients who had been treated with intrathecal baclofen for 1–4 years were included. For patients unable to communicate, data were collected through a proxy. The Patient Global Impression of Change was used to measure patients' general satisfaction with change from intrathecal baclofen treatment. The Life Orientation Test – revised, was used to measure general expectations/optimism. Results : General satisfaction with intrathecal baclofen treatment was high; 51/77 patients reported "much improved" or "very much improved." There was no relationship between the two main outcomes (general satisfaction and general expectations/optimism) ( r s = 0.12, p = 0.382). The two groups; those who could and those who could not communicate, did differ regarding personal characteristics and should be evaluated as such. Conclusions: Most patients/proxies reported a high level of satisfaction with intrathecal baclofen treatment. The reported satisfaction with intrathecal baclofen treatment was not dependent on general expectations. Implications for Rehabilitation: Patients with intrathecal baclofen treatment report low levels of health and quality of life at the same time as they are highly satisfied with their treatment. Intrathecal baclofen should be equally offered to both optimistic and less optimistic patients. Patients who are able to/not able to communicate, differs in characteristics and should be informed and followed up in different ways in daily clinical practice.